An analytical model for estimating spalled zone size of rolling element bearing based on dual-impulse time separation. (4th August 2019) - Luo, Maolin; Guo, Yu; Wu, Xing; Na, Jing
Abstract: The quantification of the spall zone size remains the significant challenging area in health monitoring of rolling element bearings (REBs). Size estimation for the spall zone of a rolling element bearing (REB) is playing a crucial role in bearing performance degradation assessments, damage severity evaluation and remaining useful life prediction. The conventional algorithms of spall zone size estimation are focused on establishing a robust signal processing technique to measure the width of the spall zone based on the analysis of vibrations. In this paper, a new analytical model is proposed for size estimation of the spall zone located on the outer race of a REB. An investigation into the kinematic mechanism of the passing process of the rolling element over the spall zone is carried out, the excitation mechanism of the entry and exit responses excited by a spall located on the REB outer race is studied and the contact models of rolling element-spall interaction are presented in this paper. The dual-impulse time separation (DTS) is determined from the pre-whitened vibration signal. As a result, a spall zone size estimation model which is a function of the DTS and the relationship of rolling element-spall zone interaction is developed based on the Hertzian contact theory. Experiments for four sizes of seeded spall are carried out to validate the proposed model for quantitatively estimating the spall zone size. All of the results which are given by the proposed analytical model present a good agreement with the real size of the spall width of the REB. Comparison between the estimated values of spall zone size calculated from the proposed model and the actual spall zone sizes of the rolling element bearing shows that the proposed model of spall zone size estimation is effective in quantifying the size of the bearing spall. Highlights: A new model for spall size estimation of the rolling element bearing is developed. Comprehensive investigation and explanation of the dual-impulse behavior are introduced. Main derivations of formula on estimating the spall size are presented. The proposed model is less biased for the rotor speed and the stiffness measurement. Spall size estimation can be effectively and accurately performed by the proposed model.